The Relationship Between Self-Talk, Anxiety, and Counselling Skill - Hiebert, Bryan; Uhlemann, Max R.; Marshall, Anne; Lee, Dong Yul (Canadian Journal of Counselling and Psychotherapy, 2007)
Ninety-five participants from two graduate counsellor training programs were assessed onanxiety level, self-talk, and counselling skill. High anxiety reflected high negative self-talk, low positive self-talk, and poor video-tape performance.